Opinions of Turkish veterinarians on the termination of unwanted pregnancies in dogs - Ozen, Abdullah; Sasmaz, Onur Yerlikaya; Alan, Seda Cavus (Wiley, 2024)
BackgroundNo time constraints exist in Turkish veterinary law regarding the termination of unwanted pregnancies in dogs. Having undergone limited ethical debate, opinions on this issue vary among veterinarians. This study aimed to determine appropriate indications accepted by veterinary practitioners for the termination of unwanted pregnancies in dogs and the cut-off point preferred by these professionals for performing this medical and surgical intervention.MethodsA qualitative methodology was used for the collection of the data. Interviews were conducted with 40 veterinarians (13 practitioners and 27 academics).ResultsThe main reasons for performing pregnancy termination were 'institutional obligations' and 'demand of the animal owner'. Meanwhile, the cut-off points for veterinarians were 'possibility of pregnancy', 'implantation/diagnosability/visibility', 'heartbeat' and 'viability'.LimitationsThe inclusion of ethics experts among the authors may have caused bias in the comments of the participants on ethical issues.ConclusionThe fact that animals are legally relegated to the custody of humans not only adds a unique character to the veterinary ethical debate but also creates a comfort zone for veterinarians not willing to examine compelling ethical issues.
Keywords: animal ethics; dog; termination of unwanted pregnancy; veterinarian